Comparative Analysis of the Venom Proteome of Four Important Malaysian Snake Species - Jaya Vejayan, Palliah; Too, Lay Khoon; Halijah, Ibrahim (BioMed Central, 2014)
Naja kaouthia, Ophiophagus hannah, Bungarus fasciatus and Calloselasma rhodostoma are four venomous snakes indigenous to Malaysia. In the present study, their proteomic profile by two-dimensional gel electrophoresis (2-DE) have been separated and compared.